Does Temperature Affect COVID-19 Transmission? - Kassem, Aly Zein Elabdeen (Frontiers in Public Health, 2020)
This study utilizes the non-linear least squares method to estimate the impact of temperature on COVID-19 cases per million in forty-three countries, divided into three groups as follows: the first group is composed of thirteen countries that announced the first COVID-19 cases in January 2020, while the second and third groups contain thirteen and seventeen countries that witnessed the pandemic for the first time in February and March of the same year, respectively. This relationship was measured after four-time periods from the date of reporting the first case until April 1, April 15, May 15, and July 8, 2020, respectively. The results show an inverse relationship between COVID-19 cases per million and the temperature in the studies of the four-time periods for the three-country groups. These results were only significant statistically (p<0.1) after 110.8, 164.8 days on average from the beginning of the pandemic in the case of "January" countries.